2004
DOI: 10.1101/lm.74504
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Action in Prefrontal Cortex in the Late Stage of Memory Consolidation

Abstract: These experiments investigated the role of the noradrenergic system in the late stage of memory consolidation and in particular its action at ␤ receptors in the prelimbic region (PL) of the prefrontal cortex in the hours after training. Rats were trained in a rapidly acquired, appetitively motivated foraging task based on olfactory discrimination. They were injected with a ␤ adrenergic receptor antagonist into the PL 5 min or 2 h after training and tested 48 h later. Rats injected at 2 h showed amnesia, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 24 publications
5
82
0
2
Order By: Relevance
“…We found a time window during SWS ϳ2 h after the rat learned the odorreward contingency when the noradrenergic neurons of the locus ceruleus, which are usually quiescent during SWS, show a surge of activity that is never seen in animals that have not been in the learning situation (Sara et al, 2005). Learning-related delayed release of noradrenaline in forebrain neurons (Tronel et al, 2004), which are potentially engaged in reactivation during sleep, would serve as an effective signal or "molecular switch" for gene expression during a subsequent REM episode (Ribeiro et al, 1999;Cirelli and Tononi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We found a time window during SWS ϳ2 h after the rat learned the odorreward contingency when the noradrenergic neurons of the locus ceruleus, which are usually quiescent during SWS, show a surge of activity that is never seen in animals that have not been in the learning situation (Sara et al, 2005). Learning-related delayed release of noradrenaline in forebrain neurons (Tronel et al, 2004), which are potentially engaged in reactivation during sleep, would serve as an effective signal or "molecular switch" for gene expression during a subsequent REM episode (Ribeiro et al, 1999;Cirelli and Tononi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…to disturb olfactory associative learning (Tronel et al, 2003(Tronel et al, , 2004Boix-Trelis et al, 2007;Carballo-Márquez et al, 2007) and the acquisition and extinction of gustatory aversion (Hernádi et al, 2000;Mickley et al, 2005;Akirav et al, 2006). It is also activated during TPOA retrieval (Dardou et al, 2007).…”
Section: An Effective Cs-us Association Duringmentioning
confidence: 99%
“…b-ARs include three subtypes, b1, b2, and b3, which are all present in the nervous system. Extensive behavioral and physiological studies have demonstrated that b-AR activation facilitates long-term potentiation (LTP) (Katsuki et al 1997;Lin et al 2003;Straube et al 2003;Gelinas and Nguyen 2005;O'Dell et al 2010;Connor et al 2011) and enhances memory (Ji et al 2003;Tronel et al 2004;Lemon et al 2009;Miranda et al 2011).…”
mentioning
confidence: 99%